Manajemen Program BAKU (Baik dan Kuat) di Pendidikan Diniyah Forma Daarut Tauhid Bandung - Ilham Agustian Widia Yusuf; G. Ginanjar Masruri; Cucu Munawaroh; Aan Hasanah; Bambang Samsul Arifin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Moral and character education is an urgent necessity in responding to the moral crisis among the younger generation in the modern era. This study aims to describe the character education model for students (santri) through the BAKU Program (Baik dan Kuat – Good and Strong) at Daarut Tauhiid Islamic Boarding School. This research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation study. The findings reveal that the BAKU Program is implemented in an integrated manner through value habituation, exemplary behavior, and continuous supervision. The core character values developed include honesty, responsibility, discipline, independence, and manners. Supporting factors of the program’s success include the strong pesantren culture, active role of mentors, and consistent caregiving system. The BAKU Program has proven effective in shaping students’ character holistically in spiritual, social, and emotional aspects. This study recommends that similar models be replicated in other Islamic educational institutions with adjustments to local contexts.